IMPROVING THE WORK PERFORMANCE OF AGRICULTURAL EXTENSION WORKERS THROUGH INCREASING CAPACITY, WILLINGNESS, AND OPPORTUNITY - Indriyani, Yufina Risti; Yurisinthae, Erlinda; Dolorosa, Eva (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
The implementation of development is inseparable from the agricultural sector, which is closely related to extension activities. The performance of extension workers plays a role in determining the success of extension activities. Performance measurement is needed so the organization can make the right decisions for further development.  This research aims to determine the factors that affect the performance of agricultural extension workers in Kubu Raya Regency using the Work Performance Theory. Primary data were collected through questionnaires and interviews of respondents with survey methods to identify and analyze the performance of agricultural extension workers using PLS-SEM. The determination of respondents used the census method with the subject of research of 62 agricultural extension workers in Kubu Raya Regency as the second largest rice production center in West Kalimantan. The analysis showed that the exogenous latent variables positively and significantly influence work performance. The research found factors that affect the performance of agricultural extension workers in Kubu Raya Regency include: work experience, knowledge, age, motivation, task characteristics, attitude towards work, perception of the role of extension workers, actions of coworkers, the need for information, compensation, working conditions, organizational policies and time. The efforts can be made to improve performance, such as Training of Trainers, basic and technical training, placing extension workers on their competencies, giving rewards, utilizing of Cyber Extension websites, and strengthening the role and function of BPP.